Margins are central: identity and indigenous resistance to colonial globalization in Guam. Issue 3 (27th May 2021) - Montón-Subías, Sandra; Dixon, Boyd
ABSTRACT: Early modern colonial globalization was the first producer of marginality and cultural erasure on a world scale. The CHamorus of Guam and Marianas know this well since they were the first Pacific islanders to be turned into indigenous 'others' by European colonial powers. In a certain sense, investigating Guam is like investigating a huge terrain vague, or an interstice or in-between space that exists outside the cultural, social, and economic dynamics acknowledged by the Global North. However, it is within these margins where vibrant resistance to global cultural standardization settles and happens, as CHamorus also know. In this article, we will focus on CHamoru cultural resilience at lånchos (rural properties outside cities and villages), at reducciones (villages or towns where CHamorus were forcibly nucleated in the seventeenth century), and at the current use of colonial 'ruins' to promote indigenous cultural enhancement and community wellbeing.